THE IMPORTANCE OF SUGAMMADEX AT POSTOPERATIVE RESIDUAL NEUROMUSCULAR BLOCK - Bryam Esteban Coello García,; Diana Carolina Martínez Pesántez,; Erick Alberto Ortíz Mora,; Sven Petronio Muñoz Vélez,; Esteban Fabricio Torres Soliz,; Paula Belén Alvarez Orellana, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Introduction: postoperative residual neuromuscular blockade is the postoperative muscle paralysis caused by incomplete or null antagonism of neuromuscular blocking agents. Post-surgical residual paralysis (PORP) has a high incidence and may cause adverse effects, increasing postoperative morbidity and mortality. The gold standard for complete reversal of neuromuscular blockade is a T4/T1 ratio of 0.9. Small degrees of paralysis are associated with an increased risk of postoperative pulmonary complications. Recent research indicates that residual neuromuscular blockade is a significant risk factor for patient safety. Objective: to detail the current information related to postoperative residual paralysis, in addition to explaining the use and characteristics of sugammadex in its reversal. Methodology: a total of 45 articles were analyzed in this review, including review and original articles, as well as clinical cases, of which 35 bibliographies were used because the other articles were not relevant for this study. The sources of information were PubMed, Google Scholar and Cochrane; the terms used to search for information in Spanish, Portuguese and English were: postoperative residual neuromuscular block, postoperative muscle weakness, sugammadex, anticholinesterase inhibitors. Results: Neuromuscular block occurs due to muscle fragility in the postoperative period due to antagonism, which produces a decrease in the musculature of the upper and lower airways. When this phase is properly managed, extubation delays are reduced, and postoperative pulmonary complications are reduced. Sugammadex is a relaxant that decreases the possibility of persistent neuromuscular paralysis; as neuromuscular blockade increases, contraction decreases. Therefore, when this drug is used, the risk of adverse effects, mostly respiratory, is avoided. This drug inactivates rocuronium, and the adverse effects it presents (although very infrequent) are dysgeusia, cough, grimacing or increased secretion through the endotracheal tube. Conclusions: sugammadex is suggested to be used before neostigmine, although it should be used in patients with high risk of postoperative complications, such as patients over 80 years of age or with post cardiothoracic surgery. However, sugammadex reverses neuromuscular blockade more rapidly, with a decrease in the frequency of residual neuromuscular blockade and postoperative pulmonary complications such as pneumonias. A point to consider is that sugammadex is more expensive and is usually accompanied by higher presentations of adverse effects.